Rejuvenating Tithonus. (14th June 2013) - Loh, Kyle M; Lim, Bing
Abstract : Four recent publications, including one in this issue by Surani and colleagues, report that Prdm14 preserves the pluripotent stem cell state by inhibiting FGF signalling and global DNA methylation.